2006
DOI: 10.1262/jrd.16084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Culture and Embryo-culture Conditioned Medium on Development of Bovine Embryos

Abstract: Abstract.We investigated the effect of group culture on bovine embryo development, and also investigated the effect of embryo-culture conditioned medium on developmental competence of individually cultured bovine embryos. Slaughterhouse-derived bovine oocytes were matured and fertilized in vitro. The presumptive zygotes were cultured individually or cultured in groups of 2 to 5 embryos with a constant culture density (5 µl/embryo). After 7 days of culture, the rates of embryos developed to the blastocyst stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
69
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 34 publications
7
69
1
3
Order By: Relevance
“…Another possibility could be to modify directly the composition of culture media with the use of cell co-cultures (bovine oviduct epithelial cell, Lim and Hansel, 1996;granulosa cells, O'Doherty et al, 1997;cumulus cells, Goovaerts et al, 2009), conditioned media (Fujita et al, 2006) or addition of GF (Paria and Dey, 1990;Carolan et al, 1996;Lim and Hansel, 1996;Brison and Schultz, 1997). The review by Hardy and Spanos (2002) clearly reflects the importance of a number of GF affecting preimplantation embryo development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility could be to modify directly the composition of culture media with the use of cell co-cultures (bovine oviduct epithelial cell, Lim and Hansel, 1996;granulosa cells, O'Doherty et al, 1997;cumulus cells, Goovaerts et al, 2009), conditioned media (Fujita et al, 2006) or addition of GF (Paria and Dey, 1990;Carolan et al, 1996;Lim and Hansel, 1996;Brison and Schultz, 1997). The review by Hardy and Spanos (2002) clearly reflects the importance of a number of GF affecting preimplantation embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when embryos were cultured individually or in reduced groups, in addition to a lower efficiency of embryo production, the obtained embryos usually presented a lower number of cells per blastocyst (Paria and Dey, 1990;O'Doherty et al, 1997; Nagao et al, 2008: 5 v. 25 embryos). Numerous authors have previously indicated, in several mammalian species, that IVEP efficiency is negatively affected when a single or a low number of oocytes/embryos were in vitro cultured in comparison with a higher number of the same (Paria and Dey, 1990;Lane and Gardner, 1992;Carolan et al, 1996;O'Doherty et al, 1997;Fujita et al, 2006). Moreover, we have observed that post-fertilisation culture, especially the last part of the culture period, seems to be the most important period for bovine embryo development when single and/or low numbers (5 to 10) of embryos were cultured (Salvador et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En los animales domésticos como el bovino, uno de los principales problemas a los que se enfrenta la fertilización in vitro es el bajo porcentaje de blastocistos viables obtenidos a partir de ovocitos madurados in vitro (5,6) . De acuerdo a la experiencia de diversos grupos de investigación (7)(8)(9), en los sistemas bovinos, del total de ovocitos que se someten a maduración in vitro (IVM) sólo se logra obtener aproximadamente un 40 % de blastocistos viables; lo que es muy diferente a lo observado a partir de ovocitos madurados in vivo, donde el porcentaje de blastocistos viables obtenidos es cercano al 80 % . Esto sugiere que la IVM modifica el microambiente del ovocito, al ocasionar un cambio celular y genético que impide que esta célula se desarrolle de manera normal (10) .…”
Section: Introductionunclassified
“…In domestic animals like cattle, one of the main problems faced by in vitro fertilization is the low percentage of viable blastocysts derived from in vitro matured oocytes (5,6) . According to the experience of different research groups (7)(8)(9) in cattle systems, the total number of oocytes undergoing in vitro maturation (IVM) only manages to get about 40 % of the viable blastocysts; versus in vivo matured oocytes, where the percentage of viable blastocysts obtained is close to 80 %. This suggests that the IVM modifies the microenvironment of the oocyte, to cause cellular and genetic change that prevents this cell to develop as normal (10) .…”
Section: Introductionmentioning
confidence: 99%